What Makes A Good Teacher? Exploring Student-Teachers’ Perceptions - Dilafruz Sarimsakova (Indonesian Journal Publisher, 2026)
This article explores student-teachers' perceptions of what makes a good teacher. Drawing on qualitative written reflections and online comments, the study examines how future teachers define effective teaching and which qualities they consider most important in classroom practice. The findings show that student-teachers do not define a good teacher only through subject knowledge. Instead, they describe good teaching as a combination of knowledge, clear explanation, creativity, engagement, patience, emotional support, fairness, motivation, adaptability, and passion for teaching. The strongest finding is that student-teachers view good teachers as professionals who make learning understandable, interesting, and emotionally safe. Participants emphasised that a good teacher explains difficult ideas simply, uses interactive methods, encourages learners, respects individual differences, and creates a classroom where students are not afraid to make mistakes. These findings support recent literature which conceptualises effective teaching as multidimensional, combining content knowledge, supportive learning environments, student engagement, and reflective professional growth. A good teacher is therefore not only a transmitter of knowledge, but also a facilitator of learning, a motivator, a caring adult, and a reflective professional who helps students grow academically and personally